A MOOC-Integrated Design Thinking Model for Hearing-Impaired Learners - Kanyarat Sriwisathiyakun (Journal of Information Technology Education Research, 2024)
Aim/Purpose: This study aims to introduce an innovative approach to improving learning outcomes for hearing-impaired learners (HL) within inclusive education settings. By integrating design thinking principles into Massive Open Online Courses (MOOCs) specifically designed for HL, this research seeks to address their unique educational needs. The study examines the components of a design thinking model within MOOCs for HL and evaluates the effectiveness of the pilot course in enhancing their learning experience and achieving the required test scores. Background: The persistent educational disparities faced by HL necessitate innovative solutions within inclusive education. By employing a design thinking approach, educational tools were developed specifically for these learners, with the empathy phase profoundly understanding and addressing their unique needs and desires. This study aims to bridge this gap by leveraging design thinking principles and MOOCs tailored for HL alongside instructional strategies and Universal Design for Learning (UDL) techniques. Methodology: The study unfolds in three primary phases: Model Development, Model Assessment, and Model Piloting. In the Model Development phase, design thinking principles are integrated with Thai MOOC development, instructional strategies, and UDL techniques to create the initial model. The Model Assessment phase involves expert evaluations to validate and refine the model based on their feedback. Finally, in the Model Piloting phase, the refined model is tested with learners, and assessments are conducted to evaluate its practical applicability and effectiveness in a real-world setting. Contribution: This research contributes significantly to reducing educational inequalities and advancing inclusive education. By introducing a model that integrates design thinking principles into MOOCs tailored for HL, it promotes lifelong learning opportunities and aligns with broader societal efforts to address educational disparities. Findings: Key findings from the study include the development of a comprehensive six-stage model and its essential co-components, which received high suitability ratings from expert evaluations. The model’s application resulted in an impressive pass rate among learners, highlighting its effectiveness in enhancing learning outcomes. These results demonstrate the model’s potential to impact inclusive education significantly by providing a scalable and effective framework for integrating design thinking into MOOC development. Furthermore, it creates courses that effectively meet the diverse needs of learners, ensuring accessibility and improved learning experiences for all. Recommendations for Practitioners: Practitioners should adopt design thinking and UDL principles in MOOC development, ensuring courses are tailored to HL needs. Engage HL communities for relevant feedback and focus on accessibility with assistive technologies. Implement scalable solutions for broader impact and regularly assess course effectiveness to promote lifelong learning opportunities. Recommendation for Researchers: Researchers should continue to explore and refine the developed model, considering its application across diverse educational contexts and populations. Collaboration with HL communities and stakeholders can provide valuable insights for enhancing the effectiveness of inclusive education interventions. Impact on Society: The integration of design thinking principles into MOOCs tailored for HL has a profound impact on society by promoting equal educational opportunities and lifelong learning. By addressing educational disparities, this research contributes to creating a more inclusive and equitable society. Future Research: Future research could focus on longitudinal studies to assess the long-term impact of the model for HL. Additionally, exploring innovative technologies and pedagogical approaches can enhance the effectiveness of inclusive education interventions. Collaborative research efforts across disciplines can advance the field of inclusive education and foster continuous improvement in learning outcomes for diverse populations.
Keywords: Diverse Interdisciplinary Research Innovations; Subtitles and Audiovisual Media; Hearing Impairment and Communication